Predictors for being offered epilepsy surgery: 5-year experience of a tertiary referral centre. Issue 2 (2nd May 2015) - Fois, Chiara; Kovac, Stjepana; Khalil, Aytakin; Tekgöl Uzuner, Gülnur; Diehl, Beate; Wehner, Tim; Duncan, John S; Walker, Matthew C
Abstract : Objectives: To define factors that predict whether patients with pharmacoresistant focal epilepsy are offered epilepsy surgery (including invasive EEG) and the main reasons for not proceeding with these after non-invasive presurgical evaluation. Methods: We retrospectively analysed data from 612 consecutive patients with focal epilepsy admitted to a video-EEG Telemetry Unit for presurgical evaluation, and used a multivariate logistic regression model to assess the predictive value of factors for being offered potentially curative surgery. Results: In the multivariate analysis, bilateral lesions on MRI (OR: 0.10; 95% CI 0.03 to 0.24), no lesion (OR: 0.33; 95% CI 0.22 to 0.49) or extratemporal lobe epilepsy (OR: 0.30; 95% CI 0.20 to 0.45) were the only factors that significantly reduced the probability of being offered surgery. 32% of patients who were offered epilepsy surgery decided against proceeding. Conclusions: There was a low chance (<10%) of being offered surgery if there were bilateral lesions on MRI and extratemporal lobe epilepsy. Patients should be given advice on the risk/benefit ratio and of realistic outcomes of epilepsy surgery; this may help reduce the number of patients who refuse surgery after comprehensive workup.